Manufacturing Method of High-Purity Solid Fuel Briquettes Using Carbon Sludge, a By-product of the Lithium-Ion Battery Recycling Process
Patent Information
- Application Number
- KR1020260095494
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-05-27
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2046-05-27
Smart Images

Figure 112026064000035-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing high-purity solid fuel coal using carbon sludge, a byproduct of a waste lithium-ion battery recycling process. More specifically, the invention relates to a method for manufacturing high-purity solid fuel coal using carbon sludge, a byproduct of a waste lithium-ion battery recycling process, characterized by mechanically and chemically activating carbon sludge generated in a black mass wet leaching process, a waste lithium-ion battery recycling process, mixing it with a composite binder, and high-pressure molding, thereby increasing the recycling efficiency of waste resources and manufacturing solid fuel coal with excellent calorific value. Background Technology
[0003] Generally, the recycling process for spent secondary batteries involves mechanically crushing and sorting the waste batteries after discharge and dismantling to recover black mass, which is concentrated with valuable metals. In this process, the black mass, from which the current collector and outer casing have been removed through the thermal decomposition of the binder and specific gravity / magnetic separation, is subsequently recovered as strategic minerals such as lithium and nickel through a wet process. However, the carbon sludge, which is a carbonaceous component remaining after the recovery of valuable metals in the wet leaching process, is simply landfilled or treated as low-grade fuel due to its high moisture content and impurity content.
[0004] Furthermore, a certain amount of electrolyte components remains within the black mass even after the physical crushing and sorting processes of spent secondary batteries. This is because the electrolyte is strongly adsorbed within the porous structure of the electrode active material due to capillary forces, and organic solvents are trapped within the polymer structure due to the swelling of the electrode binder. This residual electrolyte forms organic byproducts during subsequent wet processes, becoming a major cause of the deterioration of the physical properties of the carbon sludge.
[0005] Thus, the inventor intends to manufacture high-strength, high-heat-dissipation industrial fuel coal that can replace fossil fuels while ensuring the physical and chemical stability of carbon sludge through a high-efficiency molding technology, which is a mechanochemical grinding method capable of safely solidifying it and increasing energy density.
[0007] In addition, the general process of recovering black mass from waste batteries and discharging carbon sludge is as follows.
[0009] First, the collected waste battery packs and modules undergo a discharge process to remove residual electrical energy. This is intended to fundamentally prevent the risk of fire and explosion that could occur during physical crushing, and the voltage is typically lowered to an inactive state by immersing them in an electrolyte solution (brine) or using a discharge resistor. Once discharge is complete, the batteries undergo a dismantling stage to remove housings and wires, and are then separated into individual cells. The separated battery cells are then fed into a mechanical device for crushing and grinding processes. This process involves coarse crushing to initially expose and volatilize the internal electrolyte, followed by a fine grinding process to induce the active materials of the positive and negative electrodes to be physically and completely detached from the aluminum and copper foils acting as current collectors. At this stage, polymer binders (such as PVDF) used during electrode manufacturing remain firmly adhered to the surface of the active material particles, and due to the porous structure of the electrodes and the swelling of the binders, organic electrolyte components remain within the pores. To effectively remove residual electrolyte and binder components, the pulverized material is transferred to a heat treatment (drying) process. This process, conducted at a temperature ranging from approximately 300 to 500°C, thermally decomposes the binder to neutralize the bonding force between the active material and the current collector, while simultaneously evaporating residual organic solvents to increase the purity of the powder. The mixture, after heat treatment is complete, is fed into a sorting process utilizing differences in particle size and specific gravity. After separating the iron outer casing using magnetism, light separators and plastic fragments are removed through wind sorting. Subsequently, large aluminum and copper foils are filtered out through a vibrating sieving process, and finally, a fine black powder called Black Mass is recovered, which is a mixture of lithium, nickel, cobalt, and manganese oxides, as well as the graphite and conductive material of the cathode.
[0010] At this stage, the process of recovering valuable metals from black mass proceeds as an advanced wet smelting process in which the metals are converted into a liquid state using a strong acid solvent and then individual metals are separated based on differences in chemical properties. First, a leaching process is performed in which the recovered black mass is immersed in a strong acid solvent, such as sulfuric acid or hydrochloric acid, to dissolve the valuable metal components into an ionic state. During this process, reducing agents such as hydrogen peroxide are added to maximize the dissolution efficiency of the metals and effectively dissolve the metals in oxide form. In the solution after leaching is complete, impurities originating from battery casings or current collectors, such as iron, copper, and aluminum, coexist with lithium, nickel, and cobalt. Therefore, a purification process is conducted to remove these impurities by precipitating them in the form of oxides or hydroxides through stepwise pH adjustment or the addition of oxidizing agents.
[0011] The filtrate from which impurities have been removed is transferred to a solvent extraction process using organic solvents. In this stage, manganese, cobalt, nickel, etc., are sequentially separated and concentrated using extractants with different selective binding forces for each metal ion. Finally, a precipitating agent, such as sodium carbonate or sodium hydroxide, is added to each separated metal solution to induce a chemical reaction, thereby ultimately recovering high-purity compounds such as lithium carbonate, nickel sulfate, and cobalt sulfate. The graphite remaining undissolved during all these chemical reaction processes is discharged in the form of carbon sludge while retaining a high moisture content.
[0013] This invention has a new purpose and effect without significantly altering the manufacturing equipment of the activation device among the components of the patent registered by the applicant under Republic of Korea Registration No. 10-2903886, dated December 19, 2025.
[0015] The above-described activation device comprises a rectangular base plate (11), a rotary motor (12) formed on the upper part of the base plate (11), and
[0016] A rotary movable part (10) including a rotary shaft (13) coupled to the rotary motor (12);
[0018] A first activation part (20) comprising a first body (21) including an input port (23) eccentrically coupled to the rotation shaft, a spring (S) formed at the bottom of the first body (21) that moves left, right, up, and down due to an eccentric load when the first body (21) rotates, and a crushing ball (22) formed inside the first body (21) that can crush a material located inside the first body (21) and enable primary activation through a collision action that occurs by moving irregularly up, down, left, and right due to the rotation of the first body;
[0020] A second body (31) formed integrally by contacting one side of the first body (21), a cylindrical mesh net (M) formed between the first body (21) and the second body (31), and
[0021] A spring (S) formed at the bottom of the second body (31) and moving left, right, up, and down due to an eccentric load when the first body (21) rotates, and
[0022] A second activation part (30) comprising a crushing core (32) formed long in the horizontal direction, which is formed inside the second body (31) and allows for secondary activation by crushing a material located inside the second body (31) through a collision action that occurs by moving irregularly up, down, left, and right due to the rotation of the second body;
[0024] A third body (41) formed integrally by contacting one side of the second body (31), a cylindrical mesh net (M) formed between the second body (31) and the third body (41), and
[0025] A spring (S) formed at the bottom of the third body (41) and moving left, right, up, and down due to an eccentric load when the third body (41) rotates, and
[0026] A crushing ball (42) formed inside the third body (41) and capable of activating a third substance located inside the third body (41) by crushing it through a collision action that occurs as the third body (41) moves irregularly up, down, left, and right due to the rotation of the third body (41), and
[0027] It includes a third activation unit (40) comprising an outlet (43) through which the above-mentioned third activated material is finally crushed and mixed, passes through a mesh screen (M), and discharged as a final raw material.
[0029] In addition, the activated grinding device is referred to as a mechanochemical process (MCP) or a mechanochemical grinding process, and in this invention, it is referred to as a three-section mechanochemical grinding.
[0030] This is an advanced process that converts physical stress generated during the milling process—caused by high-energy collisions between grinding cores or balls and raw materials—into chemical energy. Going beyond simple particle size reduction, this technology falls within the core category of reactive chemistry, inducing reduction by inducing direct chemical reactions in solid-solid or solid-liquid phases. The mechanical energy input during the grinding process is consumed by plastic deformation that destroys the crystal structure of the particles, leading to severe disturbance of the crystal lattice and amorphization. This structural collapse rapidly increases the internal energy of the particles, maximizing thermodynamic activity and consequently dramatically improving fundamental physical properties such as solubility and sinterability. In other words, this process is a mechanochemical control technology that fundamentally alters the physicochemical state of particles by continuously applying strong mechanical stress to the material, enabling the induction of reactivity and the creation of novel properties that are difficult to achieve with conventional thermal processes. Prior art literature
[0033] Republic of Korea Registration No. 10-2903886 (Registration Date: December 19, 2025) The problem to be solved
[0034] To achieve the above objective, the present invention aims to manufacture a method for producing high-purity solid fuel coal utilizing carbon sludge, a byproduct of the waste lithium-ion battery recycling process, characterized by mechanically and chemically activating carbon sludge after a black mass wet leaching process, mixing it with a composite binder, and high-pressure molding, thereby increasing the recycling efficiency of waste resources and producing solid fuel coal with excellent calorific value. means of solving the problem
[0036] To solve the above problem, the present invention comprises the steps of: preparing carbon sludge, which is a carbonaceous residue remaining after valuable metals are recovered in a wet leaching process of black mass (S1); manufacturing tertiary activated carbon sludge by performing three-section mechanochemical grinding through an activation device to promote chemical stability of the carbon sludge (S2); and manufacturing tertiary activated carbon sludge with a moisture content of 5% or less by vacuum drying the tertiary activated carbon sludge (S3); Step (S4) of preparing a tertiary activated hydrocarbon-based polymer waste resource or a tertiary activated waste resource mixture by three-section mechanochemical crushing and stirring of one selected from hydrocarbon-based polymer waste resources or waste resource mixtures through an activation device, and preparing a tertiary activated composite binder by mixing one selected from the tertiary activated hydrocarbon-based polymer waste resource or tertiary activated waste resource mixture with a starch binder in a weight ratio of 7:3; and mixing the tertiary activated carbon sludge with a moisture content of 5% or less and the tertiary activated composite binder in a weight ratio of 8:2, and then feeding the mixture into a molding machine to produce 130 Kgf / cm² 2 A method for manufacturing high-purity solid fuel coal using carbon sludge, a byproduct of a waste lithium-ion battery recycling process, is provided, characterized by including the step (S5) of compressing to a pressure above. Effects of the invention
[0038] According to the present invention, by recycling waste lithium-ion battery black mass leaching residue (carbon sludge) that was previously treated as waste and waste resources, it is possible to drastically reduce landfill and treatment costs and realize a resource-circulating model.
[0040] According to the present invention, by applying a three-section mechanochemical activation process rather than simple grinding to maximize combustion efficiency and physical properties through mechanochemical activation, the physical and chemical structure of carbon sludge and waste resource particles is modified to increase combustion reactivity even though they are waste, thereby significantly improving the total calorific value, durability, and efficiency of the fuel coal produced through this process. Brief explanation of the drawing
[0042] Figure 1 is an actual photograph of a fuel coal produced by the method of manufacturing high-purity solid fuel coal using carbon sludge, a byproduct of the spent lithium-ion battery recycling process. Figure 2 is a graph of the total calorific value according to the method for manufacturing high-purity solid fuel coal using carbon sludge, a byproduct of the spent lithium-ion battery recycling process. FIG. 3 is a diagram of an activation device according to a method for manufacturing high-purity solid fuel coal using carbon sludge, a byproduct of the waste lithium-ion battery recycling process. Specific details for implementing the invention
[0043] Below, we will examine the specific details of each step.
[0045] Before explaining, the present invention comprises a rectangular base plate (11), a rotary motor (12) formed on the upper part of the base plate (11), and
[0046] A rotary movable part (10) including a rotary shaft (13) coupled to the rotary motor (12);
[0048] A first activation part (20) comprising a first body (21) including an input port (23) eccentrically coupled to the rotation shaft, a spring (S) formed at the bottom of the first body (21) that moves left, right, up, and down due to an eccentric load when the first body (21) rotates, and a crushing ball (22) formed inside the first body (21) that can crush a material located inside the first body (21) and enable primary activation through a collision action that occurs by moving irregularly up, down, left, and right due to the rotation of the first body;
[0050] A second body (31) formed integrally by contacting one side of the first body (21), a cylindrical mesh net (M) formed between the first body (21) and the second body (31), and
[0051] A spring (S) formed at the bottom of the second body (31) and moving left, right, up, and down due to an eccentric load when the first body (21) rotates, and
[0052] A second activation part (30) comprising a crushing core (32) formed long in the horizontal direction, which is formed inside the second body (31) and allows for secondary activation by crushing a material located inside the second body (31) through a collision action that occurs by moving irregularly up, down, left, and right due to the rotation of the second body;
[0054] A third body (41) formed integrally by contacting one side of the second body (31), a cylindrical mesh net (M) formed between the second body (31) and the third body (41), and
[0055] A spring (S) formed at the bottom of the third body (41) and moving left, right, up, and down due to an eccentric load when the third body (41) rotates, and
[0056] A crushing ball (42) formed inside the third body (41) and capable of activating a third substance located inside the third body (41) by crushing it through a collision action that occurs as the third body (41) moves irregularly up, down, left, and right due to the rotation of the third body (41), and
[0057] An activation device is used that includes a third activation unit (40) comprising a discharge port (43) through which the above-mentioned third activated material is finally crushed and mixed and discharged as a final raw material by passing through a mesh screen (M).
[0059] The second body crushing core (32) has a diameter of 10 to 20 mm and a length of 100 to 200 mm, and the third body crushing ball (42) has a diameter of 5 to 10 mm.
[0061] In addition, the first body crushing ball (22) used in the present invention requires weight because it must strike coarse particles first, and since crushing energy that initially breaks large lumps is key, it has a diameter of 15 to 25 mm, and
[0062] The second body crushing core (32) has an excellent horizontally elongated shape that has the effect of ‘rubbing’ carbon sludge and binder, and plays a role in pushing starch and wax into the carbon pores, so it is made with a diameter of 10 to 20 mm / a length of 100 to 200 mm.
[0063] The third body crushing ball (42) has a diameter of 5 to 10 mm. This is because, in the final stage, even very fine particles must be activated, so as the number increases, the number of contacts with the particles increases, causing the homogeneity to rise vertically.
[0065] In addition, the three-section mechanochemical grinding referred to in the present invention means mechanochemical grinding that undergoes a grinding process in three stages.
[0067] [Step (S1) of preparing carbon sludge, which is a carbonaceous residue remaining after valuable metals are recovered in the wet leaching process of black mass]
[0069] This step is a step for preparing carbon sludge, which is a carbonaceous residue remaining after valuable metals are recovered in the wet leaching process of black mass, a waste lithium-ion battery recycling process.
[0071] More specifically, the first step (S1) is a step of collecting insoluble carbon residue remaining after leaching valuable metals from black mass obtained through crushing and sorting of waste lithium-ion battery scrap, and the carbon sludge is composed of a composite carbonaceous component mixed with natural graphite, artificial graphite, and carbon black for conductive materials.
[0073] [ Step (S2) of producing tertiary activated carbon sludge by performing three-section mechanochemical grinding through an activation device to promote chemical stability of the above carbon sludge.
[0075] This step is a step of producing tertiary activated carbon sludge by performing three-section mechanochemical grinding through an activation device to promote chemical stability of the carbon sludge.
[0076] The above S2 step is a step of applying strong mechanical shear force and impact to carbon sludge using an activation device, characterized by intentionally disrupting the crystal structure of the particles to form an amorphous carbonaceous precursor with maximized thermodynamic activity. The internal stress of the particles generated during this process acts as a driving force to induce chemical reactivity, thereby promoting bonding with binder components during the molding of solid fuel coal.
[0078] More specifically, carbon sludge originally has a very hard and stable crystal structure, so if you try to burn it, it does not burn well or mix well with other substances.
[0079] However, if this structure is forcibly broken through mechanochemical crushing (MCP), the number of 'active sites' where bonds between atoms are broken increases, which improves the bonding strength with polymer waste resources later on. Additionally, since the irregular amorphous structure reacts with oxygen more rapidly than a regular crystalline structure, the combustion power can be improved. In particular, because it becomes slightly 'softened' rather than a hard crystal, it becomes easier to maintain the form of a solid fuel when pressed under high pressure.
[0081] In other words, graphitic carbon, which is the main component of carbon sludge, possesses a high degree of crystallinity due to sp² covalent bonding, so the bonding strength with other materials is significantly reduced by general physical mixing alone. Therefore, the key of the present invention is to forcibly shake this rigid crystal lattice through strong mechanical stress to convert stable carbon into an 'unstable and highly reactive' state.
[0083] Let's examine the three-section mechanochemical grinding process step by step.
[0085] [Step of introducing carbon sludge into the first body (21) constituting the activation device;]
[0086] [Step in which the first body (21), the second body (31), and the third body (41) are eccentrically rotated by the rotating movable part (10), and the spring (S) formed at the bottom of each of the first body (21), the second body (31), and the third body (41) moves up and down and left and right under the eccentric load, thereby forming vibrations in the first body (21), the second body (31), and the third body (41);]
[0087] [The step of eccentrically rotating the first body (21) and simultaneously generating internal vibration by a spring (S) so that the crushing ball (22) positioned inside moves irregularly within the first body (21), causing the carbon sludge and the crushing ball (22) inside the first body (21) to collide and crush to perform primary activation and produce primary activated carbon sludge;]
[0089] Each step of the activation process begins by introducing carbon sludge into the first body (21) that constitutes the activation device.
[0090] The carbon sludge introduced initially forms an aggregated coarse particle structure characteristic of black mass, but as the rotating operating part (10) is driven, the first body (21), the second body (31), and the third body (41) all begin eccentric rotation and receive powerful physical energy.
[0091] At this time, the spring (S) provided at the bottom of each body receives an eccentric load and generates complex vibrations in all directions (up, down, left, and right). These vibrations induce a fluidized state that suspends the raw materials and crushing media inside the device, thereby fundamentally preventing the phenomenon of raw materials sticking to the walls that occurs during a simple rotation process.
[0092] At the same time, inside the first body (21), crushing balls (22) with a diameter of 15 to 25 mm located inside the device jump irregularly and repeatedly collide at high speed with the fluidized carbon sludge.
[0093] The powerful crushing impact force generated during this process enables mechanochemical polishing (MCP) that physically destroys the rigid graphitic crystal lattice (sp² bond) of carbon sludge.
[0094] As the crystal structure of the particles is intentionally shaken and microscopic cracks occur, and a large number of 'active sites' with maximized reactivity are created at the sites where bonds between atoms are broken, the carbon sludge is transformed into primary activated carbon sludge, which is thermodynamically unstable but has very high chemical reactivity.
[0096] [The step of moving the above primary activated carbon sludge to the second body (31) by a physical method through vibration and rotation by passing through the cylindrical mesh net (M) formed between the first body (21) and the second body (31);]
[0097] [Regarding the step of manufacturing secondary activated carbon sludge by causing the primary activated carbon sludge moved to the second body (31) to be secondarily activated by the vibration generated as the spring (S) moves up, down, left, and right under an eccentric load, and the crushing core (32) formed horizontally inside vibrating and moving in a circle due to the rotation of the second body (31), thereby colliding and crushing the primary activated carbon sludge;]
[0099] The primary activated carbon sludge, which has secured fluidity through physical impact and shearing phenomena in the first body (21), passes through a cylindrical mesh net (M) located between the first body (21) and the second body (31) using the continuous vibration and rotational force of the device as power.
[0100] At this stage, the mesh screen (M) acts not merely as a passage but as a particle size separator, and by selectively moving only particles that have been fined to a size or smaller and have secured reactivity to the next section, it ensures the homogeneity of the entire process and acts as a physical barrier to block the inflow of finely ground large particles.
[0101] The primary activated carbon sludge that enters the second body (31) in this way encounters a crushing core (32) with a diameter of 10 to 20 mm and a length of 100 to 200 mm, which is formed horizontally inside the body, where the eccentric vibration of the lower spring (S) and the rotational energy of the body are combined.
[0102] Unlike conventional spherical crushing balls (22), the crushing core (32) has a contact area in the form of a line or plane and vibrates and moves in a circular motion, which generates a strong shear force that strongly crushes and rubs the particles.
[0103] In this process, the carbon sludge undergoes physical deformation beyond simple impact, such as the exfoliation of particle surfaces or the maximization of internal stress, and is produced into secondary activated carbon sludge in which the reaction sites of the carbon structure are further dispersed by frictional heat and shear stress between particles.
[0104] The behavior of these crushed cores (32) plays a key modifying role in forming an optimal interface state that can maximize the bonding strength with the binder in subsequent processes by spreading the high-viscosity sludge thinly.
[0106] [A step in which the secondary activated carbon sludge naturally passes through the cylindrical mesh (M) formed between the second body (31) and the third body (41) by a physical method involving vibration and rotation and moves to the third body;]
[0107] [A step of manufacturing tertiary activated carbon sludge by colliding and crushing the 2nd activated carbon sludge as the 2nd activated carbon sludge moved to the 3rd body (41) is moved up, down, left, and right by vibrations generated as the spring (S) receives an eccentric load and moves, and as the crushing ball (42) located inside the 3rd body (41) moves irregularly due to the rotation of the 3rd body (41);]
[0108] [Regarding the step of discharging the above-mentioned third activated carbon sludge through the discharge port (43);],
[0110] The secondary activated carbon sludge, modified by receiving a strong shear force from the crushing core in the second body (31), passes through a second cylindrical mesh (M) formed between the second body (31) and the third body (41) using the continuous high-frequency vibration and rotational force of the device as power. At this time, the mesh (M) breaks the surface tension of the sludge through high-speed vibration to prevent the mesh clogging phenomenon characteristic of high-viscosity materials, and acts as a bridge in the continuous process to guide only precisely selected fine particles to the final section.
[0112] The raw material that enters the third body (41) undergoes tens of thousands of collisions with small crushing balls (42) with a diameter of 5 to 10 mm located inside, in an environment where the eccentric vibration of the lower spring (S) and the rotational energy of the body are maximized.
[0113] The small crushing balls (42) used in this stage have a much higher number of individuals than the media in the previous section, which dramatically increases the frequency of collisions with particles.
[0114] Numerous small balls (42) that jump irregularly strike the secondary activated sludge in ultra-fine units to finally homogenize the particle size, and also form fine irregularities and active radicals densely on the surface of the carbon particles to produce tertiary activated carbon sludge.
[0115] This final activation process raises the surface energy of the carbon sludge to its physical limit, thereby completing an optimal anchoring structure that allows the composite binder component to penetrate deep into the pores and adhere strongly during the subsequent molding process.
[0116] The high-purity raw material, having completed all activation processes, is drawn out to the outside through the outlet (43) by the continuous driving force of the device.
[0118] [Step (S3) of controlling the moisture content of the activated carbon sludge to 5% or less by vacuum drying the above 3rd activated carbon sludge]
[0120] Step S3 is a thermodynamic stabilization and degassing process that removes trace amounts of electrolyte and moisture remaining inside the tertiary carbon sludge activated by mechanochemical grinding in the previous step, thereby fundamentally blocking internal gas expansion and structural defects that may occur during the subsequent molding process.
[0122] First, activated tertiary carbon sludge is introduced into a closed vacuum chamber, and then the internal pressure of the system is reduced to a level of 10 to 100 Torr to create an environment that lowers the boiling point of the liquid.
[0123] According to the Clausius-Clapeyron principle, water and electrolyte solvents (EC, DMC, etc.) bound deep within the micropores of carbon by capillary force are induced to vaporize smoothly even at low temperatures.
[0124] delete
[0125] At this time, multi-stage temperature programming is applied instead of simple heating, and in the first stage, surface moisture and low-boiling point organic solvents are stably removed in the 120 to 140 ℃ range to prevent sludge scattering caused by rapid volatilization.
[0127] In the second step, the temperature is gradually increased to the range of 140 to 180 ℃ to completely extract bound water and high-boiling point residues inside the pores.
[0128] In this process, vacuum cycling gas purging technology is used in parallel to intermittently inject a small amount of nitrogen gas and re-pressurize to replace residual gas deep within the pores.
[0129] At the same time, a continuous stirring system is operated to continuously stir the tertiary activated carbon sludge, thereby maximizing the heat transfer area between carbon particles and preventing particle aggregation, and finally, by uniformly controlling the moisture content of the activated tertiary carbon sludge to 5% or less, tertiary activated carbon sludge with a moisture content of 5% or less is produced.
[0131] Carbon sludge with such optimized moisture content has activated free energy on the particle surface, forming strong intermolecular bonding forces when mixed with polymer waste resources.
[0132] As a result, this process can suppress 'internal expansion cracks' and layer separation caused by internal stress resulting from the vaporization of residual moisture during high-pressure compression in a subsequent stage.
[0133] In addition, not only is the mechanical strength of solid fuel coal improved, but unnecessary heat of vaporization loss during combustion is minimized, thereby maximizing the net calorific value as a high-purity fuel.
[0135] [Preparing a tertiary activated hydrocarbon-based polymer waste resource or a tertiary activated waste resource mixture by three-section mechanochemical grinding and stirring of either one selected from hydrocarbon-based polymer waste resources or waste resource mixtures through an activation device, and
[0136] Step (S4) of manufacturing a tertiary activated composite binder by mixing one selected from the above tertiary activated hydrocarbon-based polymer waste resource or tertiary activated waste resource mixture with a starch binder in a weight ratio of 7:3;
[0138] Before proceeding with the explanation, let us examine the reasons why each component is blended. Waste plastics composed of polyethylene (PE) and polypropylene (PP) have long hydrocarbon chains that generate high heat upon combustion; as some of these chains break, they form a strong network that traps carbon particles.
[0139] Although waste wax has a relatively lower molecular weight compared to solid PE / PP, it acts as an internal lubricant that reduces friction between particles during crushing and molding, and at the same time provides a waterproof coating effect on the surface of finished fuel coal, which can prevent disintegration caused by moisture.
[0140] While polymer waste such as coffee grounds and sawdust has a high ignition temperature, these materials generate embers by emitting volatile matter at low temperatures. In other words, they can maximize initial ignition performance.
[0141] In addition, waste tires (GTR) contain rubber components that act as an elastic binder during compression molding, preventing the fuel coal from breaking. Waste tire powder (Ground Tire Rubber, hereinafter referred to as 'GTR') refers to 'waste tires ground into powder or particle form.' That is, Ground: (past participle of Grind) ground; Tire: tire; Rubber: rubber.
[0143] The hydrocarbon-based polymer waste resource in this step is manufactured by mixing waste plastics with polyethylene (PE) components, waste plastics with polypropylene (PP) components, and waste wax in a weight ratio of 4:4:2, and
[0144] The above waste resource mixture is prepared by mixing “polyethylene (PE) component waste plastic, polypropylene (PP) component waste plastic, waste wax, coffee grounds, sawdust and waste tire powder (GTR) in a weight ratio of 3.5:3.5:1:1:0.5:0.5.
[0145] In addition, the tertiary activated waste resource, modified by passing through three sections of a first crushing ball (22), a second crushing core (32), and a third crushing ball (42) in succession, has its particles micronized and its surface energy maximized, making it an optimal state for combining with other materials.
[0146] Finally, when this tertiary activated hydrocarbon-based polymer waste resource or tertiary activated waste resource mixture is precisely mixed with a natural starch binder in a weight ratio of 7:3, a final tertiary activated composite binder is completed that strongly binds the carbon sludge particles while increasing the combustion efficiency of high-purity fuel coal. The binder produced through this process exhibits much higher bonding strength than a simple mixture, thereby ensuring the mechanical strength and durability of the solid fuel.
[0148] In addition, we will examine the specific details of manufacturing a tertiary activated composite binder through three-section mechanochemical grinding and stirring using an activation device.
[0150] [Step of introducing one type selected from hydrocarbon-based polymer waste resources or waste resource mixtures into the first body (21) constituting the activation device]
[0151] [Step in which the first body (21), the second body (31), and the third body (41) are eccentrically rotated by the rotating movable part (10), and the spring (S) formed at the bottom of each of the first body (21), the second body (31), and the third body (41) moves up and down and left and right under the eccentric load, thereby forming vibrations in the first body (21), the second body (31), and the third body (41)]
[0152] [The step of eccentrically rotating the first body (21) and simultaneously generating internal vibration by a spring (S) so that a crushing ball (22) positioned inside moves irregularly within the first body (21), and the crushing ball (22) collides with and crushes a hydrocarbon-based polymer waste resource or an activated waste resource mixture inside the first body (21) to perform primary activation and produce a primary activated hydrocarbon-based polymer waste resource or an activated waste resource mixture]
[0154] In this step, a hydrocarbon-based polymer waste resource or a waste resource mixture is introduced into the first body (21). The interior of the first body (21) is maintained in a state where a crushing medium is pre-filled in an appropriate ratio to maximize the efficiency of subsequent processes, such as crushing and grinding.
[0156] The first body (21), the second body (31), and the third body (41), which are eccentric from the vertical axis, begin to rotate at high speed by the driving of the rotating movable part (10). At this time, the spring (S) provided at the bottom of each body absorbs and repels the uneven load caused by the eccentric rotation and generates strong complex vibrations in the up-down and left-right directions. These complex vibrations convert simple rotational motion into three-dimensional irregular behavior, creating a physical environment in which the internal raw material and crushing medium can overcome the influence of gravity and become fluid.
[0158] A crushing ball (22) with a diameter of 15 to 25 mm located inside the first body (21) receives rotational force from the body and vibrational energy from the spring, and strikes the internal space irregularly. Since the crushing ball (22) used in this step must first strike the raw material in a coarse particle state, it focuses on transmitting crushing energy through a strong weight. As the crushing ball (22) collides with the raw material at a high frequency, the large lumps initially introduced are finely broken and crushed, and in this process, a primary physical activation occurs in which active points on the surface of the particles are exposed, thereby producing a primary activated material in a state suitable for subsequent processes.
[0160] [Step of moving the above primary activated hydrocarbon-based polymer waste resource or activated waste resource mixture to the second body (31) by a physical method through vibration and rotation by passing through the cylindrical mesh net (M) formed between the first body (21) and the second body (31)]
[0161] [A step of manufacturing a secondary activated hydrocarbon-based polymer waste resource or activated waste resource mixture by causing the primary activated hydrocarbon-based polymer waste resource or activated waste resource mixture moved to the second body (31) to be secondarily activated by the vibration generated as the spring (S) moves up, down, left, and right under an eccentric load, and the crushing core (32) formed horizontally inside vibrating and moving in a circle due to the rotation of the second body (31)]
[0162] [Regarding the step in which the secondary activated secondary activated hydrocarbon-based polymer waste resource or activated waste resource mixture naturally passes through the cylindrical mesh net (M) formed between the second body (31) and the third body (41) by a physical method involving vibration and rotation and moves to the third body],
[0164] The primary activated hydrocarbon-based polymer waste resource or primary activated waste resource mixture, in which starch particles are destroyed and polymer chains are cut by the impact of a large crushing ball in the first body (21), passes through a cylindrical mesh net (M) located between the first body (21) and the second body (31) using the continuous rotational force and vibration of the device as power.
[0165] In this process, the mesh (M) acts as a kind of 'sieve' by means of the device's powerful vibration energy, uniformly separating the binder components with dispersed particle sizes and transferring them to the next stage.
[0166] In particular, the vibration of the spring (S) continuously counteracts the cohesive force between particles so that high-viscosity binder components do not remain in the mesh, and a forced transport mechanism operates to push them out of the mesh (M) by physical pressure.
[0167] The primary activated hydrocarbon-based polymer waste resource or primary activated waste resource mixture transferred to the second body (31) is exposed to a new crushing environment in which the rotational energy of the body is combined with the violent up-and-down-left-right vibrations caused by the eccentric load of the lower spring (S).
[0168] At this time, the crushing core (32), which is arranged horizontally inside the second body (31), rotates in a circle and simultaneously vibrates and moves, thereby applying a strong shear stress to the binder that is distinct from the spherical crushing ball (22).
[0169] The large contact area of the crushing core (32) produces the effect of crushing and spreading the particles of primary activated hydrocarbon-based polymer waste resources or primary activated waste resource mixtures thinly, thereby producing secondary activated hydrocarbon-based polymer waste resources or secondary activated waste resource mixtures in which the waste resources and starch components are fused more densely.
[0170] The secondary activated hydrocarbon-based polymer waste resource or secondary activated waste resource mixture, which is finely crushed and modified by the action of the crushing core (32), maintains fluidity maximized by the shearing effect and reaches the second cylindrical mesh net (M) formed between the second body (31) and the third body (41).
[0171] Here, the binder naturally passes through the fine holes of the mesh through the physical vibration and centrifugal force of the device, and moves smoothly to the third body (41), which is the final homogenization stage, without any stagnation.
[0172] The repetition of such continuous movement and activation increases the chemical reactivity of the binder stepwise.
[0174] [A step of manufacturing a tertiary activated hydrocarbon-based polymer waste resource or activated waste resource mixture by colliding and crushing the secondary activated hydrocarbon-based polymer waste resource or activated waste resource mixture by the vibration generated as the spring (S) moves up, down, left, and right while receiving an eccentric load from the third body (41), and the crushing ball (42) positioned inside the third body (41) moving irregularly due to the rotation of the third body (41)] and,
[0175] [Regarding the step of discharging the above-mentioned tertiary activated hydrocarbon-based polymer waste resource or activated waste resource mixture through the discharge port (43), and mixing one selected from the above-mentioned manufactured tertiary activated hydrocarbon-based polymer waste resource or activated waste resource mixture with a starch binder in a weight ratio of 7:3 to manufacture a tertiary activated composite binder],
[0177] The secondary activated hydrocarbon-based polymer waste resource or secondary activated waste resource mixture that passes through the mesh net (M) and moves to the third body (41) is placed in a vibration environment where the lower spring (S) moves violently up, down, left, and right under an eccentric load.
[0178] At the same time, as the high-speed rotational force of the third body (41) is added, strong centrifugal force and vibration energy are superimposed in the internal space, and small crushing balls (42) with a diameter of 5 to 10 mm located inside begin to jump at ultra-high speed in an irregular trajectory.
[0179] At this stage, small crushed balls maximize the frequency of collisions with binder particles based on their overwhelmingly large number compared to the media in the existing section.
[0180] The secondary activated hydrocarbon-based polymer waste resource or secondary activated waste resource mixture is repeatedly collided and crushed between crushing balls (42) and undergoes a homogenization process in which the particle size distribution is controlled to an extremely narrow range.
[0182] The tertiary activated hydrocarbon polymer waste or tertiary activated waste mixture, after all mechanochemical modifications are completed, is drawn out to the outside through the outlet (43) by the continuous driving force and vibration of the device.
[0184] A tertiary activated composite binder is prepared by mixing a tertiary activated hydrocarbon-based polymer waste resource or a tertiary activated waste resource mixture, in which all mechanochemical modifications have been completed, with a starch binder in a weight ratio of 7:3.
[0186] The final tertiary activated composite binder manufactured in this way possesses uniform physical properties and strong adhesive strength despite being derived from waste materials, and functions as a key material that determines the final quality of high-purity solid fuel coal by firmly binding carbon sludge in subsequent processes.
[0188] [The above tertiary activated carbon sludge with a moisture content of 5% or less and the above tertiary activated composite binder are mixed in an 8:2 weight ratio, and then the mixture is fed into a molding machine to 130 Kgf / cm² 2 Step of compressing to the above pressure (S5);]
[0190] This step is a process for manufacturing a final high-purity solid fuel coal by mixing a tertiary activated carbon sludge with maximized fixed carbon content and a tertiary activated composite binder with imparted reactivity in an optimal weight ratio of 8:2 and achieving physical and chemical integration through high-pressure compression.
[0191] First, 80 wt% of tertiary activated carbon sludge, which is an energy source, and 20 wt% of a tertiary activated composite binder for bonding and combustion are mixed. Here, the weight ratio of 8:2 is a numerical limit to secure critical bonding strength that can maintain drop strength after molding while maximizing the net calorific value as a solid fuel.
[0193] If the ratio of the tertiary activated composite binder is less than 20%, the cross-linking bonding strength between carbon particles is insufficient, causing the molded body to crumble easily; if it exceeds 20%, the carbon content is relatively reduced, which may lower the heat output that lasts for a long time.
[0195] The mixture mixed in a weight ratio of 8:2 is compressed at a high pressure of 130 Kgf / cm² or more inside a molding machine mold. At this time, the carbon sludge, with a moisture content controlled to 5% or less in step S3, rapidly increases in density during the compression process without expansion resistance due to internal water vapor pressure.
[0196] Strong compressive stress of 130 Kgf / cm² or more forces waste wax and starch components within the tertiary activated composite binder to penetrate into the fine pores of the carbon particles, and in this process, a 'high-density carbon matrix' structure with minimized inter-particle gaps is formed.
[0198] In particular, the two materials, whose surface reactivity is enhanced by mechanochemical activation, promote intermolecular forces and chemical covalent bonds under high pressure, thereby acquiring strong interfacial adhesion beyond simple physical clumping.
[0199] This structural density forms a hydrophobic barrier that blocks external moisture penetration, while simultaneously controlling the release rate of volatile components during combustion to ensure a stable and long combustion time without rapid explosive combustion.
[0200] Consequently, Stage S5 is the final confirmation stage that converts waste battery byproducts into an energy source with calorific value and mechanical strength exceeding that of commercial coal through high-pressure compression technology.
[0201] Fuel coal produced by this process generates less fine dust thanks to its high-density structure and provides eco-friendly, high-efficiency energy characteristics by inducing complete combustion to minimize residual unburned fuel.
[0203] Ultimately, the principle is to overcome the physical limitations of the raw material through mechanochemical crushing despite it being waste through a step-by-step process and to regenerate it into a high-value-added resource, thereby maximizing chemical reactivity by applying strong shear stress and frictional energy to amorphize the crystal structure of the particles.
[0204] In this process, the shear thinning phenomenon is induced to secure the fluidity of high-viscosity raw materials and realize the efficiency of the continuous process.
[0205] As a result, waste-derived components bind strongly at the molecular level, creating an optimal state for the production of high-purity solid fuel coal.
[0208] Below, we will examine the test examples through Example 1, Comparative Example 1, and Comparative Example 2.
[0211] [Example 1]
[0212] First, carbon sludge is introduced into the first body (21) constituting the activation device.
[0213] Then, the first body (21), the second body (31), and the third body (41) are eccentrically rotated by the rotating movable part (10), and vibration is formed in the first body (21), the second body (31), and the third body (41) as they move up, down, left, and right while receiving the eccentric load of the spring (S) formed at the bottom of each of the first body (21), the second body (31), and the third body (41).
[0214] Next, the first body (21) is rotated eccentrically, and at the same time, internal vibration is generated by the spring (S), so that the crushing ball (22) located inside moves irregularly inside the first body (21), and the carbon sludge inside the first body (21) and the crushing ball (22) collide and crush to perform primary activation, thereby producing primary activated carbon sludge.
[0215] The above primary activated carbon sludge passes through a cylindrical mesh (M) formed between the first body (21) and the second body (31) and is moved to the second body (31) by a physical method through vibration and rotation.
[0216] The carbon sludge moved to the second body (31) receives an eccentric load from the spring (S) and moves up, down, left, and right, causing vibrations. Additionally, the crushing core (32), which is formed horizontally and located inside, moves and vibrates in a circle due to the rotation of the second body (31), causing the carbon sludge to collide and crush to be secondarily activated, thereby producing secondarily activated carbon sludge.
[0217] The above secondary activated carbon sludge naturally passes through the cylindrical mesh (M) formed between the second body (31) and the third body (41) by physical means through vibration and rotation and moves to the third body.
[0218] The secondary activated carbon sludge moved to the third body (41) moves up, down, left, and right under the eccentric load of the spring (S), and the vibration generated by this, along with the rotation of the third body (41), causes the crushing ball (42) located inside the third body (41) to move irregularly, thereby colliding and crushing the secondary activated carbon sludge to produce the tertiary activated carbon sludge and discharging it through the discharge port (43).
[0220] Next, the above-mentioned third-stage activated carbon sludge is introduced into a closed vacuum chamber, and then the vacuum is reduced to a vacuum level of 100 Torr to create a vacuum that lowers the boiling point of the liquid.
[0221] Multistage temperature control is performed, consisting of a first drying step to remove surface moisture by heating to a temperature range of 135°C under the above reduced pressure state, and a second drying step to extract residual electrolyte and bound water inside the pores by gradually increasing the temperature to 180°C.
[0222] In addition, during the above multi-stage temperature control, nitrogen gas is intermittently injected into the vacuum chamber and depressurized to replace and discharge residual gas inside the pores, while continuously stirring the tertiary activated carbon sludge to prevent aggregation between particles and increase heat transfer efficiency, thereby producing tertiary activated carbon sludge with a final moisture content of 5% or less.
[0224] Next, a waste resource mixture prepared by mixing waste plastic of polyethylene (PE) component, waste plastic of polypropylene (PP) component, waste wax, coffee grounds, sawdust, and waste tire powder (GTR) in a weight ratio of 3.5:3.5:1:1:0.5:0.5 is introduced into the first body (21) constituting the activation device.
[0225] The first body (21), the second body (31), and the third body (41) are eccentrically rotated by the rotating movable part (10), and vibration is formed in the first body (21), the second body (31), and the third body (41) as they move up and down and left and right by receiving the eccentric load of the spring (S) formed at the bottom of each of the first body (21), the second body (31), and the third body (41).
[0226] The first body (21) is rotated eccentrically, and at the same time, internal vibration is generated by a spring (S), causing the crushing ball (22) located inside to move irregularly within the first body (21), and the crushing ball (22) collides with and crushes the waste resource mixture inside the first body (21) to perform primary activation and produce a primary activated waste resource mixture.
[0227] The above primary activated waste resource mixture is moved to the second body (31) by a physical method through vibration and rotation by passing through the cylindrical mesh net (M) formed between the first body (21) and the second body (31).
[0228] The primary activated waste resource mixture moved to the second body (31) and the vibration generated while moving up, down, left, and right under the eccentric load of the spring (S), and the rotation of the second body (31) cause the crushing core (32), which is formed horizontally and is located inside, to vibrate and move in a circle, thereby colliding and crushing the primary activated waste resource mixture to produce a secondary activated waste resource mixture.
[0229] The above secondary activated waste resource mixture is moved to the third body by naturally passing through the cylindrical mesh net (M) formed between the second body (31) and the third body (41) by means of physical vibration and rotation.
[0230] The secondary activated waste resource mixture moved to the third body (41) is subjected to vibrations generated as it moves up, down, left, and right under the eccentric load of the spring (S), and the crushing ball (42) located inside the third body (41) moves irregularly due to the rotation of the third body (41), thereby colliding and crushing the secondary activated waste resource mixture to produce a tertiary activated waste resource mixture.
[0231] The above tertiary activated waste resource mixture is discharged through the discharge port (43), and the above-manufactured tertiary activated waste resource mixture and starch binder are mixed in a weight ratio of 7:3 to produce a tertiary activated composite binder.
[0232] The tertiary activated carbon sludge, with a moisture content controlled to 5% or less, is mixed with the tertiary activated composite binder in an 8:2 weight ratio.
[0233] The above mixture is fed into a molding machine at 130 Kgf / cm² 2 The fuel bullet of Example 1 was manufactured by compressing it to the above pressure, and the fuel bullet was maintained with an average length of 1.6 cm and an average length of 1.6 ± 0.2 cm.
[0235] [Comparative Example 1]
[0236] Comparative Example 1 uses the same ingredients and formulation ratio as Example 1, but is characterized by being manufactured through shearing, a general fine grinding method, without undergoing a process through an activation device.
[0238] [Comparative Example 2]
[0239] The woody biomass used in this experiment was commercially available wood pellets manufactured from Spruce trees, and standard products with an average length of 1.6 cm were selected and used. The Spruce wood pellets obtained from the source maintained an average length of 1.6 ± 0.2 cm, and samples of uniform size were secured and used for analysis to ensure the reproducibility of the experiment.
[0241] [Comparative Example 3]
[0242] The sewage sludge used in this experiment was a commercially available organic solid fuel (Bio-SRF) pellet made using more than 50% of the sewage sludge produced as a raw material. To increase the precision of comparison with the example, standard products with an average length of 1.6 cm were selected and used. The sewage sludge pellets obtained from the source were commercial products that had obtained quality certification and maintained an average length of 1.6 ± 0.2 cm. To ensure the reproducibility of the experiment, samples with the same diameter and particle size distribution as the example were secured and used for analysis.
[0244] [Comparative Example 4]
[0245] In addition, commercial anthracite coal distributed for domestic power generation was selected as a fossil fuel control group to precisely evaluate the combustion performance and carbon density of the present invention. This sample is a high-quality fuel coal possessing a high degree of carbonization, and it was pretreated to have the same physical shape as other comparative examples to control experimental variables.
[0247] [Evaluation of Physicochemical Characteristics and Combustion Performance of Fuel Coal According to the Present Invention]
[0249] 1. [Sample Preparation and Pretreatment] In order to objectively verify the performance of the fuel coal according to the present invention, samples prepared and manufactured in Example 1 and Comparative Examples 1 to 4 were used. To ensure the reproducibility of the measurement, all samples were subjected to a conditioning process for 24 hours in a constant temperature and humidity chamber maintained at a temperature of 25°C and a relative humidity of 50% before analysis, and then introduced into the analysis.
[0251] 2. [Methods for analyzing physical and chemical properties, industrial analysis, and measurement of High Heating Value (HHV)] Moisture content and ash: The moisture content and the mass fraction of residual ash after combustion in the sample were measured by thermogravimetric analysis (TGA) in accordance with ASTM D3173 and D3174 standards.
[0252] Calorific value: An adiabatic calorimeter (Bomb Calorimeter, Parr Instrument Company) was used in accordance with the KS E 3707 (Method for Measuring Calorific Value of Coal). The total energy content of the fuel was evaluated by calculating the Higher Heating Value (HHV), which includes the latent heat of condensation generated during combustion.
[0254] 3. [Evaluation of Mechanical Strength and Water Resistance] Pellet Durability Index (PDI) measured the resistance to physical damage occurring during the transportation and storage of fuel coal. 1 kg of sample was placed into a Durability Tester and rotated at a speed of 50 rpm for 10 minutes, after which the weight ratio of the sample remaining without passing through a 1.0 mm standard sieve was calculated as a percentage. For water resistance, the sample was immersed in distilled water at 20°C for 30 minutes to evaluate its shape retention in a moisture-exposed environment. Subsequently, the external shape of the sample was visually observed, and the water resistance was quantified by measuring the weight change and volume expansion rate after re-drying.
[0256] 4. [Combustion Efficiency] To determine the thermal characteristics of the fuel coal of the present invention in an actual combustion furnace, a small experimental combustion furnace (Drop Tube Furnace) was utilized for combustion conditions and combustion efficiency. Complete combustion was induced by maintaining the internal temperature of the combustion chamber at a constant 900°C, and the combustion efficiency was calculated by measuring the amount of unburned carbon generated after combustion.
[0258] Aha, let's show the results of each test in Table 1. .
[0260] item Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Moisture content (%) 4.2 5.3 5.4 5.4 5.5 Ash content (%) 12.2 15.4 16.5 22.9 18.9 Total calorific value (kcal / kg) 4,730 4,212 4.615 4,254 4,728 Grinding Strength (PDI, %) 98.2 91.4 90.5 94.1 92.1 Underwater immersion expansion rate (%) 0.8 1.9 5.1 1.5 0.2 Combustion efficiency (%) 99.2 92.1 94.7 96.1 98.12
[0263] [Analysis of Test Results and Comprehensive Review] As seen in Table 1, the fuel coal according to Example 1 of the present invention achieved a total calorific value of 4,730 kcal / kg, which is slightly higher than that of Comparative Example 4 (4,728 kcal / kg), a domestic commercial anthracite coal.
[0264] It was proven that the physical stimulation through the first to third bodies, which is the core of the present invention, induced an energy concentration effect beyond simple mixing, as the calorific value was rapidly increased by more than 12% compared to Comparative Example 1 (4,212 kcal / kg), which had the same ingredient composition but did not undergo an activation process.
[0265] In addition, the energy advantage is clearly evident in combustion efficiency, with Example 1 recording the highest efficiency of 99.2% among all control groups, demonstrating the effect of inducing complete combustion due to the expansion of the specific surface area.
[0266] In terms of mechanical properties, the crushing strength (PDI) reached 98.2%, forming a physical structure that is significantly more robust than anthracite (92.1%) or general sewage sludge pellets (94.1%). This dense internal structure led to an extremely low value of 0.8% in the water immersion expansion rate test, which means that, unlike wood pellets (Comparative Example 2, 5.1%) that show immediate shape collapse upon exposure to moisture, it has secured excellent hydrophobicity that can maintain the shape of the fuel even in extreme environments.
[0267] In addition, Example 1 significantly reduced the amount of residue generated after combustion compared to anthracite (18.9%) or sewage sludge pellets (22.9%) by controlling the ash content to 12.2%, which leads to economic advancement that increases the operational efficiency of power generation facilities and reduces post-treatment costs.
[0268] Maintaining the moisture content at the lowest level of 4.2% through multi-stage vacuum drying not only increases the reliability of the calorific value but also provides the effect of fundamentally preventing the possibility of spoilage during storage and transportation.
[0269] In conclusion, the present invention demonstrated significant effects in terms of mechanical strength, water resistance, and combustion efficiency, while maintaining a high calorific value comparable to fossil fuels through the synergy of particle modification via an activation device and a composite binder. Industrial applicability
[0291] This invention is a technology that converts by-products generated during the waste lithium-ion battery recycling process into high-value-added energy sources. Since raw material procurement is easy and mass production using existing molding equipment is possible, it has very high potential for practical application across the entire related energy and recycling industry.
[0292] No content Explanation of the symbols
[0293] Rectangular base plate (11) rotary motor (12) Rotation axis (13) Rotating movable part (10); Input port (23) First body (21) Crushing ball (22) First activation unit (20); Second body (31) Spring(S) Crushing core (32) Second activation unit (30); Third body (41) Mesh net (M) Crushing ball (42) Discharge port (43) 3rd active part (40)
Claims
Claim 1 delete Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 A step of introducing carbon sludge, which is a carbonaceous residue remaining after valuable metals are recovered in the wet leaching process of black mass during the waste lithium-ion battery recycling process, into a first body (21) constituting an activation device; a step in which the first body (21), the second body (31), and the third body (41) are eccentrically rotated by a rotating movable part (10), and vibration is formed in the first body (21), the second body (31), and the third body (41) by receiving an eccentric load from a spring (S) formed at the bottom of each of the first body (21), the second body (31), and the third body (41) while moving up, down, left, and right; and a step in which the first body (21) is eccentrically rotated and, at the same time, internal vibration is generated by the spring (S), causing a crushing ball (22) located inside to move irregularly inside the first body (21), and carbon sludge and, inside the first body (21), A step of producing primary activated carbon sludge by primary activation through collision crushing by a crushing ball (22); a step in which the primary activated carbon sludge passes through a cylindrical mesh net (M) formed between the first body (21) and the second body (31) and moves to the second body (31) by a physical method through vibration and rotation; a step in which the primary activated carbon sludge moved to the second body (31) moves up, down, left, and right while receiving an eccentric load from the spring (S) and the vibration generated by the rotation of the second body (31) causes a crushing core (32) formed horizontally inside to vibrate and move in a circle to collision crush the primary activated carbon sludge and secondary activate it to produce secondary activated carbon sludge; and a step in which the secondary activated carbon sludge passes through the cylindrical mesh net (M) formed between the second body (31) and the third body (41) through vibration and rotation A step of moving to a third body by naturally passing through via a physical method, and vibrations generated as the secondary activated carbon sludge moved to the third body (41) moves up, down, left, and right under the eccentric load of a spring (S), andA step for manufacturing a third activated carbon sludge, wherein a crushing ball (42) positioned inside the third body (41) moves irregularly by rotating the third body (41) to collide and crush the second activated carbon sludge, thereby manufacturing the third activated carbon sludge and discharging it through an outlet (43); a step for forming a depressurization of the third activated carbon sludge by introducing it into a closed depressurization chamber and depressurizing it to a vacuum level of 10 to 100 Torr to lower the boiling point of the liquid; a multi-stage temperature control step comprising a first drying step in which surface moisture is removed by heating to a temperature range of 120 to 140 ℃ in the depressurization state, and a second drying step in which residual electrolyte and bound water inside the pores are extracted by gradually increasing the temperature to a temperature range of 140 to 180 ℃ thereafter; and, during the multi-stage temperature control step, nitrogen gas is intermittently injected into the depressurization chamber and depressurized again to replace and discharge residual gas inside the pores, while simultaneously the third A step of manufacturing tertiary activated carbon sludge with a final moisture content of 5% or less by continuously stirring the activated carbon sludge to prevent aggregation between particles and increase heat transfer efficiency; a step of introducing a waste resource mixture, prepared by mixing waste plastic of polyethylene (PE) component, waste plastic of polypropylene (PP) component, waste wax, coffee grounds, sawdust, and waste tire powder (GTR) in a weight ratio of 3.5:3.5:1:1:0.5:0.5, into a first body (21) constituting an activation device; and a step in which the first body (21), the second body (31), and the third body (41) are eccentrically rotated by a rotary movable part (10), and while moving up, down, left, and right by receiving an eccentric load of a spring (S) formed at the bottom of each of the first body (21), the second body (31), and the third body (41), the first body (21), the second body (31) and A step in which vibration is formed in the third body (41), and the first body (21) is rotated eccentrically, and at the same time, internal vibration is generated by a spring (S) so that the crushing ball (22) located inside moves irregularly inside the first body (21), and the waste resource mixture inside the first body (21),A step of manufacturing a primary activated waste resource mixture by causing a crushing ball (22) to collide and crush to perform primary activation; a step of moving the primary activated waste resource mixture to the second body (31) by a physical method through vibration and rotation by passing through a cylindrical mesh (M) formed between the first body (21) and the second body (31); a step of manufacturing a secondary activated waste resource mixture by causing a crushing core (32), which is formed horizontally and located inside, to collide and crush the primary activated waste resource mixture to perform secondary activation by causing the primary activated waste resource mixture to collide and crush to perform secondary activation, and a step of manufacturing a secondary activated waste resource mixture by causing the primary activated waste resource mixture to collide and crush to perform secondary activation of the cylindrical shape formed between the second body (31) and the third body (41). A step of moving to a third body by naturally passing through a mesh net (M) by a physical method through vibration and rotation; a step of manufacturing a tertiary activated waste resource mixture by colliding and crushing the secondary activated waste resource mixture as the secondary activated waste resource mixture moved to the third body (41) moves up, down, left, and right under the eccentric load of a spring (S) and the crushing ball (42) located inside the third body (41) moves irregularly due to the rotation of the third body (41); and a step of manufacturing a tertiary activated waste resource mixture by discharging the tertiary activated waste resource mixture through an outlet (43) and mixing the manufactured tertiary activated waste resource mixture and a starch binder in a weight ratio of 7:
3. A step of preparing a mixture by mixing the tertiary activated carbon sludge, whose moisture content is controlled to 5% or less, with the tertiary activated composite binder in an 8:2 weight ratio; feeding the mixture into a molding machine to 130 Kgf / cm², 2 A method for manufacturing high-purity solid fuel coal using carbon sludge, a byproduct of a waste lithium-ion battery recycling process, characterized by including the step of compressing to a pressure above.
Citation Information
Patent Citations
Preparation method for producing sulfur-fixing agent and sulfur-fixing briquette by using waste dry battery
CN102134521B
Coal briquettes and its manufacturing method
KR1020220058067A
Manufacturing method of eco-friendly solid refuse fuel
KR1020250141394A
Coal briquettes using waste secondary batteries and manufacturing method thereof
KR102656582B1
Method for recovering valuable metals from disused kiln furniture using mechanochemical methods
KR102903886B1
